Development of Electronic Pocket Books For Immune System Material To Increase Students' Learning Motivation - Dapit Amriko Siregar; Eka Suhardi; Rifki Risma Munandar (Journal Of Biology Education Research (JBER), 2022)
The teaching and learning process certainly requires interesting media and does not tend to be boring. For this reason, it is necessary to use media that can attract students' interest by using electronic pocket book media. This study aims to determine the quality of electronic pocket books and determine the effectiveness of electronic pocket book media. This development research uses the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. The analysis stage is an analysis of the needs of students. The design stage is the making of an electronic pocket book media design. The Development stage is an assessment of the feasibility of experts, namely material experts, media experts and teachers at SMA PGRI 1 Bogor. The Implementation stage is an assessment of the feasibility of the media and the Evaluation stage is a measurement of development achievement. The results showed the feasibility level of electronic pocketbook media, according to material experts, electronic pocketbooks were included in the appropriate category, while according to high school biology teachers and students, electronic pocketbooks were included in the very feasible category. The results of the analysis of student learning motivation before and after using the media were obtained, this showed a significant difference between before and after using the media, so it can be concluded that the electronic pocket book learning media can increase students' learning motivation.